1. -16y = 64
2. Solve for y: y = -4
3. Substitute y = -4 into the first equation: x - 2(-4) = 11
4. Simplify: x + 8 = 11
5. Solve for x: x = 3
6. Substitute x = 3 into the second equation: -14y - 77 -2y = -13
7. Simplify: -16y - 77 = -13
8. Add 77 to both sides: -16y - 77 + 77 = -13 + 77
9. Simplify: -16y = 64
10. Substitute y = -4 and x = 3 into the original equations: (3, -4)
Put the steps in order that are used to solve the following systems of equations by substitution. don't give me steps in words just
put the numbers in order give me 10 steps
x - 2y = 11 --> x = 2y + 11
-16y = 64
-16y - 77 = -13
x - 2(-4) = 11
x + 8 = 11
y = -4
x = 3
-14y - 77 -2y = -13
-7 (2y + 11) -2y = -13
(3, -4)
1 answer